Analysis Conceptual Economic Acceleration in Framework Maqashid Al-Syariah: An Overview Systematic to Social Welfare (Al-Falah) - Nafi'ah, Nafi'ah; Wahidah, Maulida Agustina Hidayatul (Fakultas Syariah INSURI Ponorogo, 2026)
This study aims to analyze the draft acceleration adopted in Indonesia's fiscal policy, especially in the 2025 State Budget, and to reconstruct it within the framework of Maqashid Al-Shariah to realize a holistic social (al-falah) research. Use a qualitative approach with a systematic literature review through content analysis and a conceptual framework to the literature economy, conventional Islamic economics, as well as the document policy government. Research results show that a GDP-growth orientation and macro indicators still dominate the paradigm of accelerating the economy, and therefore are not yet capable of ensuring distributive justice, ecological sustainability, and social-spiritual welfare. Identified existence dissonance between a growth economy and a quality welfare society, marked with inequality, jobless growth, and neglect of externalities, social and environmental. Reconstruction-based Maqashid Al-Shariah offers an acceleration model for an economy oriented towards the balanced protection of religion, soul, mind, descendants, and property. Research recommends reformulation indicator development through Maqashid Development Index, strengthening policy redistributive based on zakat and taxes progressive, expansion of social protection, as well as integration of market ethics and sustainability in the national economy policy.